The Development of TVET Educator Competencies for Quality Educator - Ismail, Affero; Hassan, Razali; Abu Bakar, Aishah; Hussin, Hanipah; Mat Hanafiah, Mohd Ariff; Asary, & Lokman Hafiz (Journal of Technical Education and Training, 2018)
Malaysia is taking steps to strengthen policy guidance and regulatory frameworks for technical and vocational education and training (TVET) and to improve its governance and programme implementation for  economic transformation and sustainable development. The transformation requires that TVET educators are well prepared to face the challenges of globalization so that Malaysian educators can stand tall and be committed to support an education system that can fulfil the needs and aspirations of a nation. The objective of this paper is to propose the effective competency of a TVET Educator in Malaysia context based on the four series of focus group discussion (FGD). This paper explains the development process of the TVET Educator competencies and the final component generated from the professional and expert in TVET Educatorâ€™s Education. The outcome this study concludes the three main components namely Personal Traits and Professionalism; Teaching and Learning and Training and Technical and Innovation. The development of these competencies is to ensure that the quality TVET Educators produce competent TVET graduates who are capable to meet the requirement of industries and professional bodies. Nevertheless, it is important for the TVET providers, industries, communities and the Government to collaborate towards achieving a status of high income nation.